Above Ground Biomass Estimation of Syzygium aromaticum using structure from motion (SfM) derived from Unmanned Aerial Vehicle in Paninggahan Agroforest Area, West Sumatra - Try Surya Harapan; Ahsanul Husna; Thoriq Alfath Febriamansyah; Mahdi Mutashim; Andri Saputra; Ahmad Taufiq; Erizal Mukhtar (Universitas Andalas, 2021)
Above ground biomass (AGB) is all living organic matters above the soil including stem, seed and leaves. This study aimed to estimate the individual clove (Syzygium aromaticum) and it’s above ground biomass using Unmanned Aerial Vehicle in the Agroforestry area in Paninggahan, West Sumatra. This study used a photogrammetry method to calculate trees and estimated the AGB. We detected 257 numbers of trees based on aerial image analysis and observed 270 after we validated on ground check in the field. The result was slightly different between estimated AGB from UAV and observed AGB from our ground validation. The estimated AGB was 5.9 ton/ Ha where the surveyed AGB was 5.6 ton/Ha. The difference between estimated AGB and observed AGB was 0.3 ton/Ha.